Estetika Batik Tulis Motif “Bintang Laut” Pekalongan, Jawa Tengah (Kajian Estetika) - Fajrul Falah (Program Studi Sastra Indonesia, Fakultas Ilmu Budaya, Universitas Diponegoro, 2018)
Aesthetic research on Pekalongan batik is rare and limited. Several studies related to Pekalongan batik are studied from the economic aspect (production, distribution, and consumption) and health (disease). This study aims to reveal the aesthetics of motif batik